ANALISIS KEBUTUHAN DISTRIBUSI BARANG DENGAN MENGGUNAKAN PENDEKATAN SIMULASI MONTE CARLO - Hidayat, Agung Prayudha; Husen Santosa, Sesar; Siskandar, Ridwan; Aziz Husyairi, Khoirul (PUSAT SAINS INDONESIA, 2022)
The key to the success of the distribution of goods by connecting the internal supply chain with consumers where the internal supply chain refers to orders. The purpose of this study is to develop a model for the number of goods distribution needs in a freight forwarding company with a Goods simulation approach. The results showed that the average number of goods distribution needs was 231,444 bags. This is a reference for freight forwarding companies in sending goods related to the number of transportation modes and shipping routes